EFFORTS TO IMPROVE THE PERFORMANCE OF THE QUALITY CONTROL (QC) SECTION OF PT. X USING THE SIX SIGMA METHOD TO FOCUS ON RISK MANAGEMENT - Suwarni, Sri; Gloria, Fransisca; Rustaman, Heri; Hidayah, Ravita Nur (STIKES Telogorejo Semarang, 2024)
Introduction: The quality control (QC) process of a pharmaceutical company must be carried out following the Good Manufacturing Practices (CPOB) guidelines. Evaluation of the QC process in the pharmaceutical industry needs to be carried out to minimize notes and risks that could affect the final results of the tests carried out. Six Sigma and risk management can be used to identify defects and risks in the quality control processes carried out. The Six Sigma and risk management methods were used in this research to improve the performance of the pharmaceutical company PT. X in the Quality Control (QC) section. Method: The method used in this research is an observational method with primary and secondary data types. Data collection is carried out by interviews, observation, and documentation that focuses on defects and risks in the QC process. Data analysis uses the Six Sigma method with DMAIC stages and SPSS 25 statistical tests. Results: results of the risk management performance values of the PT QC section. X decreased by 7.7% with a DPMO value from 328,000 to 251,200 and the Six Sigma value increased from 1.95-sigma to 2.19-sigma. Statistical analysis using the SPSS 25 chi-square method shows a value of 0.005, which means there is a difference between the risk value before and after improvement. The results of the contingency coefficient test show a value of 0.803 (close to 1), which means the data obtained has a strong relationship. The data results show an increase in the performance of the Quality Control (QC) section of PT. X which can be seen from the risk value, DPMO, and sigma value